MENGGALI KEARIFAN LOKAL ADAT NATONI DI TTS - Juliana Asbanu; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the natoni tradition, an oral cultural heritage of the Atoni Meto people in South Central Timor (TTS), East Nusa Tenggara, which carries deep social, moral, and educational significance. The study focuses on exploring the forms, roles, and socio-cultural values within natoni and how these values can be applied in Social Studies (IPS) education at the elementary level. The aim is to describe the meaning of natoni, uncover its moral and social messages, and explain its connection to the goals of Social Studies learning in shaping students’ character and civic awareness. A qualitative descriptive approach was used, with data gathered through interviews with parents, families, and community members knowledgeable about natoni, as well as literature reviews from academic journals, books, and scholarly articles. Data were analyzed through the stages of reduction, presentation, and interpretation to identify key cultural and pedagogical insights. The results show that natoni acts as a form of traditional communication that teaches values of respect, responsibility, solidarity, and cooperation. These align closely with Social Studies objectives, particularly in building students’ moral and social character. Hence, natoni can be utilized as a contextual learning resource rooted in local wisdom to strengthe cultural identity and appreciation among learners.